ANALISIS RAGAM BAHASA SISWA KELAS X H SMA NEGERI 2 KOTA BENGKULU DI FACEBOOK (KAJIAN SOSIOLINGIUISTIK) - Fahmi, Yunial (UNIB Press, 2016)
This research is aimed to obtain a descriptive about Analysis of Various Students’ Language of Class X H SMA Negeri 2 Bengkulu City Used in Their Facebook of the this research is about how the theme of students’ sentences status in their Facebook are, what kind of language and non-language characteristic s of their sentences status in Facebook of students class X H are the research. The data that are collected use purposive sampling technic by taking the samples from sentence status of the students’ Facebook accounts which have been collected. The technics used in data analysis are : (1) data collecting, data presenting, (2) conclusion or verification in document. The research findings are guile diverse themes that emerge, but in a sense more positive tone expression (91,6%) consisting of : interaction, special interaction, expression activity, adage, expression of feeling, expression of feelings provoke cancern, the phrase specifically, and information. While the expression of negative feelings (8,3%). Likewise, the original identity (the original name of the account status) consists of 19 students with a percentage (79,1%) and the remaining 5 students with a pseudonym identity (account status pseudonym) by percentage (20,8%). Linguistic traits often arises is the use of regional languages, although there are also English-speaking. Non-linguistic traits characterized by the use of icons/symbols ( stiker’s or emotion) which describes the feeling.